Impact of Teacher Professional Competency and Student Learning Intensity on Student Achievement - Khairanisyah, Afifah (BiCED Proceeding, 2025)
The research investigates the impact of teacher professional competency and student learning intensity on student achievement, specifically in English subjects. The background of the issue highlights the importance of understanding how these two variables influence educational success. It emphasizes that teacher competency and student engagement are critical factors that can significantly impact students' academic performance and overall learning experiences. The novelty of this research lies in its dual focus on teacher professional competency and student learning intensity as independent variables affecting student learning outcomes. This research includes aspects of learning intensity, providing a more comprehensive understanding of the factors contributing to educational success. This quantitative research methodology uses statistical techniques to analyze data collected through questionnaires. The questionnaire consists of 35 items that the researcher adapted. The results of this research highlight the importance of increasing the intensity of student learning as an essential factor in improving educational outcomes while recognizing the role of teacher competence in the learning environment.